Acute Thrombocytopenia in Patients Treated with the Oral Glycoprotein IIb/IIIa Inhibitors Xemilofiban and Orbofiban: Evidence for an Immune Etiology - Brassard, Jacqueline A.; Curtis, Brian R.; Cooper, Richard A.; Ferguson, John; Komocsar, Wendy; Ehardt, Maria; Kupfer, Stuart; Maurath, Clement; Swabb, Edward; Cannon, Christopher P.; Aster, Richard H. (Thrombosis and Haemostasis, 2002)
Thrombocytopenic episodes occurring in 18,845 patients treated with the GPIIb/IIIa inhibitors xemilofiban and orbofiban (“fibans”) were analyzed by a blinded review panel and 73 patients were classified as having “possible fiban-induced thrombocytopenia”. When the treatment codes were broken, a significant association between drug exposure and assignment to this group was found (p <0.001). Twenty-eight (82%) of 34 archived serum samples from these patients contained fiban-dependent antibodies specific for GPIIb/IIIa, but no such antibodies were found in 61 drug treated patients not classified as having “possible fiban-induced thrombocytopenia” (p <0.001). We conclude that fiban-dependent antibodies were the major cause of acute, severe thrombocytopenia in patients judged on the basis of clinical findings to have thrombocytopenia “possibly-induced” by xemilofiban and orbofiban. Measurement of drug-dependent antibodies may be helpful in determining the basis for acute thrombocytopenia in fiban-treated patients and possibly for identification of patients at risk to develop thrombocytopenia.
Keywords: Platelets; GPIIb/IIIa inhibitors; antibodies